“NE@R”: a new resource to promote preterm infants’ development through parents-delivered guided play - Sonia Trussardi; Cecilia Naboni; Camilla Caporali; Camilla Caporali; Camilla Pisoni; Stefano Ghirardello; Simona Orcesi; Simona Orcesi (Frontiers in Public Health, 2025)
IntroductionThe huge prevalence of neurodevelopmental disorders underscores the necessity for novel, comprehensive prevention strategies for neuroprotective intervention, particularly in preterm infants. The COVID-19 pandemic has accelerated the transformation of healthcare services, emphasizing the use of digital resources. Given the rapid brain development in infants in the first 1,000 days of life and the demonstrated impact of adaptive neuroplasticity, the implementation of early and ecological interventions are essential for supporting optimal neurodevelopment in this vulnerable population. Aim of this project is to develop a digital tool for parent-led parent-based intervention and assess its feasibility and accessibility.Materials and methodsWe collected evidence on early intervention strategies for preterm infants through a non-systematic review of current literature to develop the platform and created an ad-hoc questionnaire to evaluate the tool’s feasibility and acceptability in our neurological follow-up.Results“NE@R” is a digital platform designed to support neurodevelopment through parents-delivered play. The platform offers evidence-based information, videos, and practical activities to enhance motor, cognitive, social, and language development at each developmental phase. We introduce the resource in our clinical setting and collect 100 preterm infants’ families feedback. The majority of parents reported finding the resource beneficial, with many expressing increased confidence in supporting their child’s development.DiscussionPreterm babies families’ support represents a precious field of intervention both for parents and infants at risk. “NE@R” has proven to be an effective, low-cost tool within our follow-up program, aligning with the principles of family-centered care.